Sosialisasi Pembuatan Tampilan Web Menggunakan Aplikasi Figma - Yoli Andi Rozzi; Reno Supardi; Desi Mahdalena; Indra Kanedi; Ridho Rahman Kurnianto; Dimas Aldi Romadoni (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
This community service activity aims to improve students' knowledge and skills in web interface design using Figma at SMA Pancasila Bengkulu. The main problems include limited understanding of UI design and lack of practical skills in using design tools. The solution was implemented through training and hands-on practice. The method consists of observation, preparation, implementation, and evaluation. The results indicate improved student understanding and skills in designing web interfaces. This activity enhances digital literacy and creativity.